2019
DOI: 10.1142/s179355711950075x
|View full text |Cite
|
Sign up to set email alerts
|

A key exchange protocol using matrices over group ring

Abstract: The first published solution to key distribution problem is due to Diffie–Hellman, which allows two parties that have never communicated earlier, to jointly establish a shared secret key over an insecure channel. In this paper, we propose a new key exchange protocol in a non-commutative semigroup over group ring whose security relies on the hardness of Factorization with Discrete Logarithm Problem (FDLP). We have also provided its security and complexity analysis. We then propose a ElGamal cryptosystem based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…In this section, DLP, FP, DLPFP, Centralizer, and Semiring are defined [30,33,34], and the model, structure, flow, and security goals of the system are given.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, DLP, FP, DLPFP, Centralizer, and Semiring are defined [30,33,34], and the model, structure, flow, and security goals of the system are given.…”
Section: Preliminariesmentioning
confidence: 99%
“…[29] claims that the "semi-simple algebra" structure of group rings can decipher the key exchange protocols based on DLP. [30] suggests a Factorization Discrete Logarithm Problem (FDLP)-based key exchange protocol and analyses the security and complexity. Also, an ElGamal cryptosystem is proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of SAP, we proposed in [4] a new setting, and some protocols. In our case, the platform is a twisted group ring, a new proposal in the context of group rings, that have also been recently used in cryptography in works like [3,6,5,7]. And the action proposed is the two-sided multiplication in a twisted group ring, so the problem is a variation in the twisted case of the so-called Decomposition Problem (DP), which is a generalization of the Conjugate Search Problem (CSP).…”
Section: Alice Computes P Amentioning
confidence: 99%
“…However, the security of these schemes is still a problem to be tackled. Currently, we find many new schemes [4], [5], [6], [7], [8] designed by using algebraic structures, linear groups, non-abelian groups like matrices and polynomials which are claimed to be more secure and efficient than the existing schemes. It is observed that the size of keys and storage space can be reduced by representing the plain text message as a matrix [9], [10], [11] without compromising the security.…”
Section: Introductionmentioning
confidence: 99%